The role of social welfare in supportively social safety for children deprived of family care in light of the policy of the Kingdom of Saudi Arabia - Al-Otaibi, Rahaf Mohammed (Journal of Humanities & Social Sciences, 2022)
The main objective of this study was to reveal the role of social welfare in strengthening social safety for children deprived of family care in light of the policy of the Kingdom of Saudi Arabia. It includes several sub-goals represented in determining the role of social welfare with children deprived of family care, and identifying the level of social safety for children deprived of family care, And revealing policies that guarantee the right to protection for children deprived of family care, In a theoretical review using the descriptive approach, which includes this type of studies, the study of current facts related to the nature of the phenomenon, situation or situations by looking at the published data and information. Based on the data that was observed and referenced, the results showed that social welfare has an important role with children deprived of family care. This is due to the efforts made to work to meet the needs of children deprived of family care, as much as possible, or to alleviate these needs, The results also showed that the level of social safety showed low levels in children, and this could be due to their special circumstances. Whatever efforts are made, they are in no way equivalent to caring for the child within his natural family. She revealed that the Kingdom of Saudi Arabia has clear efforts to preserve the rights of this group in the country, through the development of legislation and policies that guarantee them protection, safety and stability with the conditions in which they live. The most prominent recommendations came to train supervisors and workers with this category in order to rehabilitate them with modern methods to deal with social and psychological problems, and to coordinate with universities and research centers to study issues that affect the security and stability of this category in light of the changes of this era.